THE INTEGRATION OF TRADITIONAL AND MODERN METHODS IN STUDYING THE LEXICO-SEMANTIC FEATURES OF ENGLISH DIALECTS (Scientific journal of the Fergana State University, 2026)
This article examines the evolution of approaches to studying English dialects, focusing on lexical-semantic features and the need to integrate traditional and modern methods. The relevance of the topic is determined by the need for comprehensive documentation and analysis of dialect diversity in a changing linguistic environment. The aim of the research is to identify how combining classical dialectological methods with new sociolinguistic and corpus approaches leads to a more complete description of dialect vocabulary and its changes. The material of the study includes classical dialect atlases, modern studies of linguistic variation, and online surveys of speakers. The results show that traditional field research, when complemented by statistical and instrumental analysis, allows for a deeper understanding of the functioning of dialect vocabulary and provides scientific and practical value, from preserving dialect heritage to sociolinguistic education.